Chemoprevention: Achievements and Future Perspectives - Adeluola, Adeoluwa A; Amin, ARM Ruhul (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Cancer is the second deadliest disease in the world with very high potential of prevention. The past few decades have witnessed an increased interest in cancer chemoprevention among researchers, clinicians and the public because a successful prevention strategy could save millions of lives. This new paradigm has led to the critical evaluation of prospective chemopreventive agents including natural dietary agents, molecular targeted agents, vaccines etc. preclinically and clinically. Many dietary agents were accorded chemopreventive status based on epidemiological studies that linked their consumption to reduce cancer risk. Despite demonstrated effectiveness in preclinical and animal model studies, their safety with long-term use remains a major concern. Although more rigorous clinical trial protocols have been developed to assess candidates for chemoprevention, accrual, compliance, and retention in chemoprevention trials possess significant challenge because volunteers for such trials are healthy people with high risk of developing cancer. In this review, we critically review various preventive strategies, promising chemopreventive agents, challenges associated with successful chemoprevention and potential ways to overcome these obstacles. Dhaka Univ. J. Pharm. Sci. 20(3): 359-372, 2022 (June) Centennial Special Issue